2020
DOI: 10.1002/ece3.6952
|View full text |Cite
|
Sign up to set email alerts
|

Different landscape effects on the genetic structure of two broadly distributed woody legumes, Acacia salicina and A. stenophylla (Fabaceae)

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…However, not all species react in the same way to habitat fragmentation. Encinas-Viso et al (2020) showed that reduced forested area had a significant impact on the genetic differentiation of the Australian legume Acacia salicina but not on A. stenophylla , which inhabits largely the same area. Foré et al (1992) even found decreased genetic differentiation in post-fragmentation populations compared to pre-fragmentation populations in Acer saccharum from the USA.…”
Section: Discussionmentioning
confidence: 96%
“…However, not all species react in the same way to habitat fragmentation. Encinas-Viso et al (2020) showed that reduced forested area had a significant impact on the genetic differentiation of the Australian legume Acacia salicina but not on A. stenophylla , which inhabits largely the same area. Foré et al (1992) even found decreased genetic differentiation in post-fragmentation populations compared to pre-fragmentation populations in Acer saccharum from the USA.…”
Section: Discussionmentioning
confidence: 96%
“…Another meta‐study demonstrated that regardless of the ecological or life‐history traits of the investigated species, fragmentation is likely to negatively impact plant sexual reproduction (Aguilar et al, 2006), however, not all species react in the same manner. Encinas‐Viso et al (2020) showed that reduced forested area had a significant impact on the genetic differentiation of the Australian legume Acacia salicina but not on Acacia stenophylla , which inhabits largely the same area. Foré et al (2011) even found decreased genetic differentiation in post‐fragmentation populations compared to pre‐fragmentation populations in Acer saccharum from the USA.…”
Section: Discussionmentioning
confidence: 99%